KONSEP PENDIDIKAN PASCANATAL DALAM PERSPEKTIF ISLAM - Indahilma Mubarokah; Abdul Baits (LPPM STAI Muhammadiyah Probolinggo, 2023)
Postnatal education has an important role in the life of every child, where it is a guarantee that children can develop optimally and not experience significant difficulties in their lives. This study aims to analyze and synthesize the concept of postnatal education and how it is viewed according to Islam. The research method used is qualitative with a literature study approach with documentation study as the data collection technique. The results of the study show that the concept of postnatal education is clearly contained in the Qur'an surah At-Tahrim [66]: 6. In the interpretations of Al-Misbah and Al-Maraghi it is explained that the verse indicates the moral responsibility of both parents to be responsible to their children and to their respective spouses, as each is responsible for what he does. This form of responsibility is through educational processes in the form of inculcating good values and obedience to Allah SWT. The family as the first place of education for children plays a role in the formation of character that is ready to face the future, while the school as a formal educational institution has a role as a reinforcement of basic education and becomes a unifier to develop relationships with society that are symbiotic mutualism to realize mutual benefits without causing harm to all components.Keywords: Education; postnata; Islam